Public attitudes toward educational reforms: a study of the problem of open-mindedness - Chunikhina Svіtlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article reviews the problem of contradictory public attitude to educational reforms in connection with the phenomenon of open-mindedness. Based on the review of case studies, two major areas of conceptualization of openness of judgments have been identified. The first direction studies the openness of judgments in the context of interpersonal interaction, as a lack of prejudice against members of groups that are interpreted as “others”, willingness to tolerate “otherness” and productively interact with other people in conflict of opinions and positions. In the second direction, openness of judgment is seen primarily as a cognitive attitude to the perception of new ideas, tolerance of diversity of opinion and willingness to think outside the box (“out of box”). A sample of 230 respondents allowed to examine the relationship between cognitive (dogmatism) and personal (openness to new experiences) aspects of openness of judgment with a subjective attitude to educational reforms. Dogmatism is related to the tough judgments about educational reforms. More dogmatic respondents tend to have negative evaluations of reforms, less dogmatic ones are more likely to have no established evaluative judgments. Openness to new experiences determines the modality of assessments of educational reforms: more “open” respondents tend to be more positive about the changes that occur as a result of reforms than less “open” ones, which are characterized by a certain pessimism. It has been found that dogmatism and openness to new experiences manifest themselves in different ways in relation to educational reforms among professionals engaged in the field of education and non-professionally related to the education of respondents.